Motivational Factors of Women Person with Disability in Private Sector - DEENA JOSEPH (Journal of Social Work Education and Practice, 2023)
Disability is an umbrella term, covering impairments, activity limitations and participation restrictions. Impairment is a problem in body function or structure; an activity limitation is a difficulty encountered by an individual in executing a task or action; while a participation restriction is a problem experienced by an individual in involvement in life situations. Thus disability is a complex phenomenon, reflecting an interaction between features of a person’s body and features of the society in which he or she lives. Persons With Disabilities have the same desires and aspirations as non-disabled persons. However, achieving their desire is directly related to their disability to which they have come to terms with or accepting to live with their disability. The convention on the Rights of Person with Disabilities is a human right instrument with an explicit social development dimension. It reaffirms that all person with all type of disabilities must enjoy all human rights and fundamentals freedom on an equal basis with others. According to the National Sample Survey Organization, 1.9% of Indian population is disabled.